2008
DOI: 10.1002/mnfr.200700317
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of polyphenol-enriched apple juice extracts to identify constituents with cancer chemopreventive potential

Abstract: Apples and apple juices are widely consumed and rich sources of phytochemicals. The aim of the present study was to determine which apple constituents contribute to potential chemopreventive activities, using a bioactivity-directed approach. A polyphenol-enriched apple juice extract was fractionated by various techniques. Extract and fractions were tested in a series of test systems indicative of cancer preventive potential. These test systems measured antioxidant effects, modulation of carcinogen metabolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
3
38
0
1
Order By: Relevance
“…These results indicated that 3-hydroxy-bdamascone (4) can activate Nrf2 leading to ARE-mediated gene expression. Consistent with this finding early eluting fractions from apple extracts, which contain 3-hydroxy-bdamascone (4) [4], also potently activated Nrf2 reporter activity (data not shown). (4) stimulates Nrf2 transcriptional activity.…”
Section: Activation Of Nrf2 Signalingsupporting
confidence: 82%
See 2 more Smart Citations
“…These results indicated that 3-hydroxy-bdamascone (4) can activate Nrf2 leading to ARE-mediated gene expression. Consistent with this finding early eluting fractions from apple extracts, which contain 3-hydroxy-bdamascone (4) [4], also potently activated Nrf2 reporter activity (data not shown). (4) stimulates Nrf2 transcriptional activity.…”
Section: Activation Of Nrf2 Signalingsupporting
confidence: 82%
“…[4]) consistently enhanced the activity of QR in Hepa1c1c7 cell culture. Analyses with HPLC did not reveal the presence of phenolic compounds as potential ARE inducers in these fractions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Флавоноид кверцетин представляется в этой связи в качестве наиболее мощного модулятора активности CYP1A из всех ком-понентов яблочного сока [61,62].…”
Section: российский вестник перинатологии и педиатрии 4 2016 Rossiyunclassified
“…The importance of world apple production reached 76,000,000 tons in 2012 [6]. Besides, apple production represents 22% of phenols consumed in diet [7]. Apple skin, as a by-product of agro industry, and fruits discarded in the orchard, are the raw material that might be used as a source of phenolic antioxidants, to be added to diverse foods.…”
Section: Introductionmentioning
confidence: 99%